Society for Tennis Medicine and Science (STMS)
Website of the international Society forTennis Medicine and Science (STMS) . The STMS is an international organization of sports medicine and science experts aiming to serve as an international forum for the generation and dissemination of knowledge of tennis medicine and science. STMS in co-operation with the International Tennis Federation (ITF), the Sanex WTA TOUR (Sanex WTA), and the ATP produces the newsletter "Tennis Medicine and Science".